Ovarian Weight, Follicle Count and Retrieved Oocyte Characteristics in West African Dwarf Goat Does Experimentally Infected with Trypanosoma brucei (Nigerian Journal of Physiological Sciences, 2019)
Summary: Trypanosomosis has been described as the single largest disease entity limiting livestock development in sub-Saharan Africa. The effects on ovarian weight, follicle count and retrieved oocyte characteristics in ten West African dwarf goat does (control=5, infected=5) experimentally infected with Trypanosoma brucei were investigated. The does were fed with elephant grass and supplement (15.23% CP) daily. Infected does received 4.8x105 T. brucei intravenously and thereafter, all does were synchronized using Lutalyse®. The results showed that the differences between control and infected does for ovarian weight (0.68±0.56 g and 0.40±0.09 g) and follicle count (10.50±1.25 and 2.50±1.22), respectively were significant (P0.05). The differences in proportion between control and infected does for well-formed-oocytes (90.5% and 9.5%), completely-denuded-oocytes (30.8% and 69.2%) and proportion per group of oocytes with substantial-investment-of-cumulus (63.3% and 9.1%), respectively were significant (P0.05). These findings suggest that experimental Trypanosoma brucei infection caused reduction in ovarian weight and follicle count, number of oocytes as well as proportion of well-formed oocytes that are capable of supporting embryonic development.